Demonstration and Characterization of Cyst-Like Structures in the Life Cycle of Trichomonas vaginalis - Beri, Divya; Yadav, Priya; Devi, H. R. Nandini; Narayana, Chinmaya; Gadara, Darshak; Tatu, Utpal (Frontiers in Cellular and Infection Microbiology, 2020)
Trichomonas vaginalis is the parasitic protozoan residing in human urogenital tract causing trichomoniasis, which is the leading non-viral sexually transmitted disease. It has cosmopolitan distribution throughout the globe and affects both men and women. Lifecycle of the parasite has been traditionally described as consisting of motile and symptom-causing trophozoites. Chemical and temperature perturbations in trophozoites have been shown to aid conversion to pseudocysts, which is poorly investigated. In the current study, we show the formation of viable cyst-like structures (CLS) in stationary phase of T. vaginalis axenic culture. We used a fluorescent stain called calcofluor white, which specifically binds to chitin and cellulose-containing structures, to score for T. vaginalis CLS. Using flow cytometry, we demonstrated and quantitated the processes of encystation as well as excystation; thus, completing the parasite's lifecycle in vitro without any chemical/temperature alterations. Like cysts from other protozoan parasites such as Entamoeba histolytica and Giardia lamblia, T. vaginalis CLS appeared spherical, immotile, and resistant to osmotic lysis and detergent treatments. Ultrastructure of CLS demonstrated by Transmission Electron Microscopy showed a thick electron-dense deposition along its outer membrane. To probe the physiological role of CLS, we exposed parasites to vaginal pH and observed that trophozoites took this as a cue to convert to CLS. Further, upon co- culturing with cells of cervical origin, CLS rapidly excysted to form trophozoites which abrogated the cervical cell monolayer in a dose-dependent manner. To further corroborate the presence of two distinct forms in T. vaginalis, we performed two-dimensional gel electrophoresis and global, untargeted mass spectrometry to highlight differences in the proteome with trophozoites. Interestingly, CLS remained viable in chlorinated swimming pool water implicating the possibility of its role as environmentally resistant structures involved in non-sexual mode of parasite transmission. Finally, we showed that symptomatic human patient vaginal swabs had both T. vaginalis trophozoites and CLS; thus, highlighting its importance in clinical infections. Overall, our study highlights the plasticity of the pathogen and its rapid adaption when subjected to stressful environmental cues and suggests an important role of CLS in the parasite's life cycle, pathogenesis and transmission.